Novel pour point depressant (PPD) copolymer synthesis, characterization, and performance evaluation for wax deposition inhibition of malaysian crude oil - Basem Saeid, M Elarbe (2023)
Wax deposition in production pipelines and transportation tubing from offshore to onshore is critical in the oil and gas industry due to low-temperature conditions. The most significant popular approach to solving this issue is inserting a wax inhibitor into the channel. The objective of this study is to synthesis a novel poly stearyl acrylate-co-behenyl acrylate (SA-co-BA) pour point depressant PPD copolymer in order to improve the flowability of Malaysian crude oil. In this study, a novel (SA-co-BA) PPD copolymer was successfully synthesized by the free radical solution polymerization method. The selection of factor levels for the optimization process was obtained based on the pre-evaluation of factors using one factor at the time (OFAT). Response surface methodology (RSM) method was used to optimize the experimental factors which are reaction temperature, the initiator concentration and reaction time respectively, a constant mass ratio (1:1). The optimize conditions were obtained at reaction time of 7 h, initiator concentration of 1 wt %, and reaction temperature of 90 °C with the corresponding yield of 97.31%. The analysis of ANOVA detected R2 value of 0.9844. Evaluation of the performance of SA-co-BA with and without the addition of nano-silica particles on PPD and rheological behaviour of Malaysian crude oil were investigated. The findings showed that SA-co-BA copolymer at 1000 ppm affects the pour point temperature from 11 to 2 °C. The optimum degree of viscosity reduction (DVR) for both SA-co-BA and SiO2 nanoparticles were at 1000 ppm by 89.76% and 200 ppm 89.52%, respectively. In addition, the highest DVR was 92% at the volume ratio (3:1) of the SA-co-BA /SiO2 blend. Evaluation of the performance of novel SA-co-BA with and without the addition of nano-silica particles on wax deposition was studied. In this study, five factors have been evaluated, which are speed of rotation from 100 to 600 rpm, the temperature of a cold finger from 5 to 25 °C, duration of the experiment from 2 to 12 h, SA-co-BA concentration from 500 to 5000 ppm and concentration of nano-silica from 100 to 800 ppm. The results indicated that the highest percentage inhibition efficiency (PIE) of SA-co-BA PPD without and with nano-silica particles were 44.14% and 52.25%, respectively. The result of RSM showed a minimum wax deposit of 0.01 g obtained at 14 °C, 60 min and 1200 ppm and ANOVA detected the value of R2 was 0.9874. To further validate the wax inhibitor chosen, molecular dynamics (MD) simulation was introduced to understand the interaction between wax crystal and wax inhibitor at the molecular level. The results indicated the n-icosane wax molecules are bonded together to create a solid wax crystal with van der Waals (vdW) interaction between H57 and H60. The radial distribution function (rdf) of the H57•••H60 interaction in the binary system of SA-co-BA and NP individually are shifted from 2.75 Å to 3.25 Å. the H57•••H60 interaction in the tertiary system of n- C20H42 wax – SA-co-BA /NP is shifted from 2.75 Å to 4.75 Å. Therefore, the combinations in tertiary system had a greater possibility of inhibiting wax than their individual counterparts. As a conclusion, the findings of this study can be used to improve a reliable model for reducing wax deposits and the associated costs.